Pengaruh Literasi Keuangan dan Persepsi Kemudahan Penggunaan Terhadap Financial Technology (Studi kasus Usaha Mikro, Kecil di Kecamatan Rimbo Bujang, Kabupaten Tebo) - Luthfi Anan , Fatih; Setiawati, Rike; Lubis, Tona Aurora (Journal of Business Studies and Management Review, 2024)
Micro and Small Enterprises sector has a big influence on the economy of the people of Tebo district, especially Rimbo Bujang. However, in practice, the community structure and Micro and Small Enterprises actors in Rimbo Bujang still rarely use financial technology. According to the Indonesian Financial Services Authority (OJK), financial technology is an innovation in the financial services industry that utilizes advances in technology whose products are systems built to carry out specific transaction mechanisms. Users of financial technology continue to grow in Indonesia, but in general cash payments still dominate, including in the Tebo district, Rimbo Bujang, because some people do not recognize and master financial literacy, ease of use, and the usefulness of the technology provided. Based on this background, researchers are interested in carrying out research entitled The Influence of Financial Literacy and Perception of Ease of Use of Financial Technology with a case study of Micro and Small Enterprises in Rimbo Bujang District, Tebo Regency. The research approach used is descriptive and quantitative with the aim of analyzing the phenomenon of the influence of financial literacy and perceived ease of use on the use of financial technology in Micro and Small Enterprises. The results of this research are that there is no influence between financial literacy and the use of financial technology by micro and small business actors in Rimbo Bujang District, Tebo Regency. This is proven by the results obtained which show that the path coefficient has a negative sign 0,168, dan P-Vallues 0,161 > 0,05 daln nilai T-Statistic 0,991< 1,96 so it can be concluded that financial literacy has no effect on financial technology. So it can be stated that the hypothesis can be accepted and is rejected because the T-Statistic value is smaller than 1.96 (T-Table) and the P-Values are more than 0.05. This means that increasing awareness, knowledge, skills, attitudes and behavior of respondents regarding financial literacy without being accompanied by socialization in the use of financial technology will not affect the use of financial technology. However, there is a significant influence between the perception of ease of use of financial technology by micro and small business actors in Rimbo Bujang District, Tebo Regency. This is evidenced by the T-Statistic value of T-statistic 8,194> 1,96 (T-Table) daln nilali P-Vallue 0.000 < 0,05, which can be interpreted that the more a person's perception of ease of use is good enough, the more that person will improve their performance. use of existing financial technology. Likewise, low understanding of perceived ease of use will make someone hesitate to use something.